Ownership of Land Ownership Rights by Traditional Villages Viewed from Indonesian Law - IRIANTORO, Agung; UTAMA, I Wayan Kartika Jaya (Indonesia Strategic Sustainability, 2025)
Transfer of land rights and review of Indigenous Villages' position as land rights owners based on Indonesian positive law. This writing includes normative legal research or what is usually called 'library research', namely research by examining secondary materials or data regarding research on legal principles, research on legal systematics, research on the synchronization stages of vertical and horizontal norms, harmonization of law and legal history. The provisions of the transfer of rights to land under the UUPA as a legal act of transfer of land rights are deliberately carried out so that the right is independent of the holder and transferred to another party. Customary villages, as owners of property rights to land reviewed under the law, can be domiciled as legal subjects of land rights owners, usually found through the purchase process or other businesses. However, there is still a potential dispute over efforts to certify customary village land.